Achieving ethical excellence - Harris, Howard (Head of Management Research); Schwartz, Michael (College teacher) (Emerald, 2014)
This volume is a selection of papers from the 20th annual 'Australian Association for Professional and Applied Ethics' Conference. Topics covered include athletes as role models, sports ethics and sports governance, the separation of powers as an integrity mechanism, and virtues in just war theory.
Keywords: Business ethics.; Professional ethics.; Sports -- Moral and ethical aspects.; Separation of powers.; elektronické knihy; electronic books